Néhány megfontolandó szempont a pedagógusok munkahelyi elégedettségének javításához: az üzbég és a magyar pedagógus teljesítmény-értékelési rendszerek összehasonlító elemzése - Szűcs, Ida; Avezova, Gulmira (Pedagógusképzés, 2024)
The initiative of the Hungarian government to introduce a new teacher appraisal system within the whole-scale teacher assessment made us review the operational teacher career models and teacher appraisal frameworks linked to salary schemes in the world and compare the planned Hungarian model with the Uzbek teacher career model and teacher appraisal framework. The comparison includes the evolution of appraisals, their procedures, criteria, and methodology. Our study proposes some ideas for decision-makers to consider when introducing or modifying teacher assessment frameworks so that they can better contribute to teachers' well-being and to improving the quality of work in education.